Understanding the determinants of vaccine hesitancy among adolescents: a systematic review. (20th October 2021) - Messina, R; Cadeddu, C; Castagna, C; Lanza, TE; Sapienza, M; Chiavarini, M; de Waure, C
Abstract: Background: The WHO defines vaccine hesitancy (VH) as 'a delay in acceptance or refusal of vaccines despite the availability of vaccine services'. In spite of the models explaining VH and the tools used to address it, VH still represents a current problem and has been declared one of the top ten global health threats by WHO in 2019. This is mainly true for the adolescents who represents 25% of the global population. This systematic review aims to address the determinants of VH in this target population. Methods: PubMed, Web of Science and Scopus were searched to retrieve articles, published in English, assessing adolescents' attitudes and confidence towards vaccinations with any study design (qualitative or quantitative) from the inception until Dec 2020. A methodological quality assessment of the articles was performed based on the study designs. Results: Out of 14, 704 articles, 20 studies were included in the qualitative analysis. Ten out of 20 studies were evaluated as of "good quality", while nine had "moderate quality" and only one had "poor quality". Factors associated to a positive attitude towards vaccination included knowledge of vaccine preventable diseases, the awareness of vaccines, their efficacy, safety and free of charge, higher education level and active involvement in decision-making. An association between VH and socio-economic conditions was also highlighted. Conclusions: This systematic review elucidated a better understanding of the determinants of VH among the adolescent population. Adolescence represents a crucial phase of life in which boys and girls begin to make significant choices about their health and develop attitudes and behaviours that continue into adulthood. Indeed, their concerns and needs in respect to vaccination should be widely examined and taken into consideration to plan tailored interventions to promote vaccination and reduce VH. Key messages: Vaccine hesitancy among adolescents is a major global health priority. This problem is little studied and further studies and initiatives aimed at increasing awareness of the problem should be deserved.